Laparoscopic Ureteroureterostomy vs. Common Sheath Ureteral Reimplantation in Children With Duplex Kidney Anomalies - Gerwinn, Tim; Gnannt, Ralph; Weber, Daniel M.; Gobet, Rita; Mazzone, Luca (Frontiers in Pediatrics, 2021)
Purpose: Laparoscopic ureteroureterostomy (LUU) has been proposed as an alternative to common sheath ureteral reimplantation (CSUR) in children with symptomatic duplex kidneys. However, data is limited for LUU in the pediatric population. The aim of this study was to analyze our experience with LUU and to compare results with those after CSUR to assess, weather a less invasive surgical approach could be a valid alternative. Patients and Methods: Data of all children with duplex kidneys who underwent either LUU or CSUR at our center from 2006 to 2018 was reviewed retrospectively. After parental counselling, the option of LUU was provided as an alternative to CSUR for unilateral procedures and in absence of vesicoureteral reflux (VUR) to the receiving ureter. Baseline characteristics, indication for surgery, hospitalization and operative times, intraoperative, postoperative, and late complications were analyzed. Preoperative and 1-year postoperative sonographies were reviewed by a pediatric radiologist. Increasing renal pelvic diameter (Δ > 5mm) was regarded as a sign of ureteral obstruction. Results: Forty children were included in this study, with 16 children receiving LUU and 24 children receiving CSUR. The children had a mean age of 2.7 years (7 m.–9.8 yr.) and were followed up in our outpatient clinic for an average of 3.85 years (3 m.–10.6 yr.) after surgery. The median hospital stay was two days shorter after LUU. Initially, considerably longer time was needed for LUU, but after more experience was gained, similar operative times were observed for both procedures. Complications were encountered in both groups. After LUU, 2 patients developed anastomotic leakage, 1 was managed conservatively, and 1 required temporary nephrostomy. In the CSUR group, 1 patient developed vesicoureteral obstruction during follow-up and required reoperation with LUU. The occurrence of postoperative urinary tract infections (UTIs) was similar in both groups. No complications arose related to the ureteral stump after LUU. Conclusion: LUU is a safe and efficacious treatment option for children with duplex kidney anomalies and can be used as an alternative to CSUR. All children receiving LUU showed a non-obstructive, patent anastomosis and no signs for stenotic compromise of the receiving ureter.